A Cross-cultural Comparison of ELT Curricula of Senior Secondary Schools in Mainland China and Hong Kong: A Governmentality Perspective - Su, Xiaoli; Ruisz, Dorottya; Zhang, Xiao (Nordic Journal of Comparative and International Education (NJCIE), 2024)
English holds significant importance as a foreign language in Mainland China and Hong Kong, where ongoing curriculum revisions are shaped by economic and sociocultural advancements. Previous research on English Language Teaching (ELT) curriculum comparisons in Asia has frequently overlooked the exploration of underlying sociocultural and socio-political factors that contribute to the observed similarities and differences. Adopting a governmentality Perspective informed by Dean's analytics of government theory, this cross-cultural comparative study investigates the ELT curricula in senior secondary schools in Mainland China and Hong Kong. Through this analysis, the study explores how sociocultural and socio-political factors interact to influence the educational landscapes. By examining the dimensions of problematizations, rationalities, techne, and teleology within the curricula, the research uncovers common challenges, rationales, approaches, and objectives, as well as distinctions arising from the unique sociocultural, political, and economic contexts of Mainland China and Hong Kong. This examination underscores the profound impact of these contextual factors on ELT curriculum design, contributing valuable insights to the cross-cultural discourse. Furthermore, the findings lay the groundwork for future research and policy development in the realm of ELT curricula, emphasizing the need for additional studies employing diverse methods and focusing on the implemented and experienced curriculum in senior secondary schools to provide a comprehensive understanding of English language education in both Mainland China and Hong Kong.